The rules of management : a definitive code for managerial success - Templar, Richard, 1950-2006. (Harlow, England ; New York : Pearson/Prentice Hall Business, 2005)
This book cover what you say and what you do (and what you seen to be doing) and show you how to ininspire your team to perform(and what you do when it doesn't) underpin your successful behaviour and actions.
Includes bibliographical references.
aug 28/05/13
Loans
Keywords: Management; Executives; Executive ability